Convalescent plasma therapy in an immunocompromised patient with multiple COVID‐19 flares: a case report. Issue 12 (9th November 2021) - Karaolidou, Frini; Loutsidi, Natasa‐Eleni; Mellios, Zois; Jahaj, Edison; Eleftheriou, Konstantinos; Pagoni, Maria; Mpaltadakis, Ioannis; Dimopoulos, Athanasios‐Meletios; Kalomenidis, Ioannis; Pappas, Apostolos G.
Abstract: Convalescent plasma (CP) transfusion has been utilized as a salvage therapy in immunocompromised patients with severe COVID‐19 pneumonia. We describe the case of a 45‐year‐old immunocompromised patient, who received CP, in order to control multiple COVID‐19 flares and prolonged SARS‐CoV‐2 viraemia lasting for 2 months after the initial diagnosis. Abstract : We describe the case of a 45‐year‐old immunocompromised patient, who received convalescent plasma, in order to control multiple COVID‐19 flares and prolonged SARS‐CoV‐2 viraemia lasting for 2 months after the initial diagnosis.